Berlinerapokryfen eller Apocryphon Berolinense/Argentoratense (ApoBA) - tidligere kendt som Frelserens Evangelium (Gospel of the Savior) - Nielsen, Jesper Tang (Dansk Teologisk Tidsskrift, 2015)
Three manuscripts (P. Berol. 22220, Strasbourg Copte 5-7, Qasr el-Wizz Codex) contain a text that was formerly known as The Gospel of the Savior. This article provides an introduction to and a translation of the three manuscripts. Recent research has raised considerable doubt about the genre and dating of the text. In the first publications it was presented as a second century gospel, but is now seen to belong to Coptic piety literature from the fifth or sixth centuries. Therefore, the article uses the newly suggested name: Apocryphon Berolinense/Argentoratense.